Computational evaluation of optoelectronic, thermodynamic and electron transport properties of CuYZ2 (Z= S, Se and Te) chalcogenides semiconductors - Mohammed Elamin Ketf; Mohamed Issam Ziane (UNIVERSITE MSILA, 2022)
Due to their useful physical properties, copper-based chalcogenides materials are recently promising for numerous emerging technological fields. In photovoltaics, discovering and designing suitable materials for solar cells is a primary technical challenge. The structural, electrical, optical, and thermoelectric properties for both CuYSe2 and CuYTe2 in the hexagonal phase, as well as CuYS2 in the orthorhombic phase have been investigated using a numerical Full Potential-Linearized Augmented Plane Wave (FP-LAPW) technique based on Density Functional Theory (DFT). To compute the structural properties, both, the local density approximation (LDA) and the generalized gradient approximation (PBE-GGA) were used as exchange-correlation potentials. On the other hand, the modified Becke-Johnson (mBJ) was used to compute the optoelectronic, properties with higher degree of precision. Our calculations revealed that these three compounds have indirect band gaps in the range of 0.6 eV–2.1 eV. Moreover, numerous thermoelectric qualities of the investigated compounds estimated as a function of chemical energy at different temperatures using the semi-local Boltzmann transport theory, whereby the findings exhibit a higher Seebeck coefficient for CuYS2 compared to CuYZ2(Z = Se and Te) up to 2.7 mV/K for CuYS2 at 300 K, with acceptable values of thermal and electronic conductivity. The quasi-harmonic model is used to examine thermodynamic properties such as heat capacity at constant pressure and volume, entropy, Debye temperature, and thermal expansion coefficient under both pressure and temperature influences. As a result of this study, CuYS2, CuYSe2 and CuYTe2 are promising materials for optoelectronic devices, especially as photovoltaic materials in solar cells.
Keywords: TB-mBJ Seebeck coefficient Electrical and thermal conductivity coefficients Dielectric function Absorption coefficient Reflectivity Heat capacity Thermal expansion coefficient